“Sharing” tourism as an opportunity for territorial regeneration: the case of Iseo Lake, Italy - Belotti, Sara (Hungarian Geographical Bulletin, 2019)
The spread of sharing economics platforms in the world of travels has highlighted the little known phenomenon of the rental of houses and apartments with a non-enterprise management. These accommodations in Italy do not require any guest registration or start-up notification, but the use of websites such as Airbnb has led to a heated debate among the actors operating in the travel and tourism industry. In fact, the regulatory vacuum and the easy-to-use websites would help circumvent the rules in order to “hide away” some business activities. Based on these assumptions, this paper analyses the case of Iseo Lake in the Northern Italy, pointing out the discussions about this new trend in travels and involving not only economic and legal aspects, but also social issues that cannot be ignored. The paper presents “sharing tourism” as an opportunity for territorial regeneration in destinations characterized by the presence of few hotel facilities, but also of many empty apartments.